A comprehensive analysis of adverse drug reactions in 2020–2023: case studies - Zhai, Jinghui; Yan, Hongzhe; Zhang, Jinping; Yan, Huiyu; Ma, Jie; Zhang, Sixi (Frontiers in Pharmacology, 2025)
IntroductionAdverse drug reactions (ADRs) have posed significant threats to patient safety and could potentially result in adverse clinical outcomes.MethodsIn this study, we analyzed ADRs data reported by a large hospital spanning from 2020 to 2023, with a particular focus on identifying demographic and clinical factors associated with severe ADRs. The dataset encompassed 5,644 cases, incorporating variables such as patient age, gender, smoking and drinking history, allergies, medication type, and administration route.ResultsAmong these, 408 cases of severe ADRs underwent detailed examination. Additionally, the study delved into the correlation between adverse drug reactions symptoms (ADRS) and various drug types. According to research statistics, individuals in the middle-aged group (46–65 years) exhibited the highest proportion of severe ADRs at 36.77%. Females were significantly more affected than males, accounting for 66.67% of severe ADRs. Anti-tumor drugs emerged as the primary cause of severe ADRs, responsible for 52.70% of such incidents. Compared with other administration methods, intravenous injection was more prone to causing severe ADRs, with a likelihood of 53.92%. Furthermore, the blood system was identified as the ADRS where severe ADRs occurred at a significantly higher rate than other parts of the body, at 53.19%. Correlation analysis reveals a strong association between medication type and factors such as patient age, administration route, and ADRS. Notably, ADRS was also strongly linked to drug type, gender, and age.ConclusionThese findings collectively highlight the critical need for personalized treatment plans and targeted monitoring. Particular attention should be directed towards high-risk groups, such as middle-aged females and patients undergoing anti-tumor therapies. By doing so, it is possible to enhance drug safety and minimize the occurrence of severe ADRs.